NPV-BSK805, an Antineoplastic Jak2 Inhibitor Effective in Myeloproliferative Disorders, Causes Adiposity in Mice by Interfering With the Action of Leptin - Haissaguerre, Magalie; Ferriere, Amandine; Clark, Samantha; Guzman-Quevedo, Omar; Tabarin, Antoine; Cota, Daniela (Frontiers in Pharmacology, 2018)
The pathophysiology of body weight gain that is observed in patients suffering from myeloproliferative neoplasms treated with inhibitors of the janus kinase (Jak) 1 and 2 pathway remains unknown. Here we hypothesized that this class of drugs interferes with the metabolic actions of leptin, as this hormone requires a functional Jak2 signaling. To test this, C57BL/6J chow-fed mice received either chronic intraperitoneal (ip) or repeated intracerebroventricular (icv) administration of the selective Jak2 inhibitor NVP-BSK805, which was proven efficacious in treating polycythemia in rodents. Changes in food intake, body weight and body composition were recorded. Icv NVP-BSK805 was combined with ip leptin to evaluate ability to interfere with the action of this hormone on food intake and on induction of hypothalamic phosphorylation of signal transducer and activator of transcription 3 (STAT3). We found that chronic peripheral administration of NVP-BSK805 did not alter food intake, but increased fat mass and feed efficiency. The increase in fat mass was more pronounced during repeated icv administration of the compound, suggesting that metabolic effects were related to molecular interference in brain structures regulating energy balance. Accordingly, acute icv administration of NVP-BSK805 prevented the ability of leptin to decrease food intake and body weight by impeding STAT3 phosphorylation within the hypothalamus. Consequently, acute icv administration of NVP-BSK805 at higher dose induced hyperphagia and body weight gain. Our results provide evidence for a specific anabolic effect exerted by antineoplastic drugs targeting the Jak2 pathway, which is due to interference with the actions of leptin. Consequently, assessment of metabolic variables related to increased fat mass gain should be performed in patients treated with Jak2 inhibitors.